Uji Antibakteri Ekstrak Bonggol Nanas Madu (Ananas Comosus L.Merr) terhadap Bakteri Porphyromonas Gingivalis - Chasanah, Niswatun; Saadah, Nikmatus; Triana, Dita Eri (Bhakta Dental Journal, 2023)
Background : Porphyromonas gingivalis is an anaerobic gram-negative bacterium which has the ability to penetrate into the gingival sulcus so that it can cause periodontal pockets in periodontal disease. Riskesdas data shows that the prevalence of periodontal disease in Indonesia reached 74.1% for all age groups. Extract of Honey Pineapple tubers (Ananas comosus L.Merr) contain active compounds, namely the enzyme bromelain and secondary metabolite compounds which have the potential to be antibacterial which can inhibit bacterial metabolism and cause death of the bacteria. Objective: To determine the antibacterial effect of honey pineapple tuber extract (Ananas comosus L.Merr) on Porphyromonas gingivalis. Research Method: This type of research is an in vitro laboratory experiment with a post-test only control group design. The sample size using the Federer formula obtained 10 treatment groups with a total population sampling technique of 30 samples. Results: A concentration of 0.78% is the Minimum Inhibitory Level (MIC) and at a concentration of 6.25% is the Minimum Kill Level (MBC). Conclusion: Honey pineapple tuber extract (Ananas comosus L.merr) has antibacterial power against Porphyromonas gingivalis bacteria. Keywords: Ananas comosus L. Merr, Antibacterial, Porphyromonas gingivalis